Music and emotion—a composer's perspective - Douek, Joel (Frontiers in Systems Neuroscience, 2013)
This article takes an experiential and anecdotal look at the daily lives and work of film composers as creators of music. It endeavours to work backwards from what practitioners of the art and craft of music do instinctively or unconsciously, and try to shine a light on it as a conscious process. It examines the role of the film composer in his task to convey an often complex set of emotions, and communicate with an immediacy and universality that often sit outside of common language. Through the experiences of the author, as well as interviews with composer colleagues, this explores both concrete and abstract ways in which music can bring meaning and magic to words and images, and as an underscore to our daily lives.